2019
DOI: 10.1177/0333102419840777
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic accuracy of headache measurement instruments: A systematic review and meta-analysis focusing on headaches associated with musculoskeletal symptoms

Abstract: Aim To systematically review the available literature on the diagnostic accuracy of questionnaires and measurement instruments for headaches associated with musculoskeletal symptoms. Design Articles were eligible for inclusion when the diagnostic accuracy (sensitivity/specificity) was established for measurement instruments for headaches associated with musculoskeletal symptoms in an adult population. The databases searched were PubMed (1966–2018), Cochrane (1898–2018) and Cinahl (1988–2018). Methodological qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 73 publications
(365 reference statements)
0
10
0
Order By: Relevance
“…An international Delphi study found that physiotherapists evaluate several musculoskeletal impairments of the cervical spine related to joint-biased interventions, e.g., manual joint palpation, cervical flexion-rotation test, cervical range of motion, passive physiological intervertebral movements, reproduction/resolution of headache symptoms and combined movement tests [27]. A recent meta-analysis concluded that the cervical flexion-rotation test has a pooled sensitivity of 0.83 (95%CI 0.72-0.94) and specificity of 0.82 (95%CI 0.73-0.91) for the assessment of patients with CeH [28]. In addition, the high prevalence of neck pain in primary headaches, such as TTH and migraine [29], may also benefit from joint-biased interventions.…”
Section: Scientific Evidence Of Joint-biased Interventions For Headachesmentioning
confidence: 99%
“…An international Delphi study found that physiotherapists evaluate several musculoskeletal impairments of the cervical spine related to joint-biased interventions, e.g., manual joint palpation, cervical flexion-rotation test, cervical range of motion, passive physiological intervertebral movements, reproduction/resolution of headache symptoms and combined movement tests [27]. A recent meta-analysis concluded that the cervical flexion-rotation test has a pooled sensitivity of 0.83 (95%CI 0.72-0.94) and specificity of 0.82 (95%CI 0.73-0.91) for the assessment of patients with CeH [28]. In addition, the high prevalence of neck pain in primary headaches, such as TTH and migraine [29], may also benefit from joint-biased interventions.…”
Section: Scientific Evidence Of Joint-biased Interventions For Headachesmentioning
confidence: 99%
“…Results of the search and the process of screening and selecting studies for inclusion in the review will be presented in a flow diagram described by PRISMA-P guidelines 27 28…”
Section: Methodsmentioning
confidence: 99%
“…Two systematic reviews24 25 have attempted to assess the usefulness of physical examination and manual examination, respectively, for the differential diagnosis of CGH, and a further systematic review26 was directed at elucidating which examination tests can be useful to detect musculoskeletal impairment in migraine sufferers. In addition, another systematic review27 assessed diagnostic accuracy of headache measurement instruments. Although for migraine all of these tools were questionnaires, and the diagnostic accuracy of only one physical test was evaluated for CGH.…”
Section: Introductionmentioning
confidence: 99%
“…Content: The questions of the HSQ cover the following subjects: frequency of headaches, frequency of headache attacks, days with headaches, the timespan of the headache crisis, characteristic of the headache (pulsating, tight, burning, one or both sides of the head), the severity of the headaches, activities that worse the headache and avoidance of activities due to headache [54,55].…”
Section: Headache Screening Questionnaire (Hsq)mentioning
confidence: 99%
“…How to obtain: The English version of the HSQ is available in the manuscripts previously published [54,55] (Figure 1).…”
Section: Practical Applicationmentioning
confidence: 99%